2016
DOI: 10.1111/jfpp.12849
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of Natural Antioxidants in Feed to Enhance the Oxidative Stability and Quality of Broiler Breast Meat and Nuggets

Abstract: Natural antioxidants efficiently increase the shelf life of meat. Lipid peroxidation decreases in meat when natural antioxidants supplemented in feed and hence there is increase in stability of meat. This project has been designed to determine a-lipoic acid (ALA), a-tocopherol and wheat germ oil (WGO) effect on growth parameters, antioxidant activity, physico-chemical analysis and sensory attributes of breast nuggets. The broilers were fed on WGO gain higher body weight and better FCR. The physico-chemical ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…The outcomes showed that the TBARS value was higher in cooked in contrast with the raw beef patties and value increased with the passage of storage intervals which is in agreement with the findings of Arshad et al (2017a). The results depicted that raw and cooked beef patties have minimum TBARS value where combination of WGO (4.5%) and WBF (3%) was used and is in line with the findings of Arshad et al (2017b) where nuggets made from wheat germ oil have minimum TBARS value.…”
Section: Resultssupporting
confidence: 90%
“…The outcomes showed that the TBARS value was higher in cooked in contrast with the raw beef patties and value increased with the passage of storage intervals which is in agreement with the findings of Arshad et al (2017a). The results depicted that raw and cooked beef patties have minimum TBARS value where combination of WGO (4.5%) and WBF (3%) was used and is in line with the findings of Arshad et al (2017b) where nuggets made from wheat germ oil have minimum TBARS value.…”
Section: Resultssupporting
confidence: 90%
“…Broiler meat is not only an affordable source of protein with low levels of collagen, essential vitamins (mainly thiamin, vitamin B6 and pantothenic acid) and minerals (iron, zinc, and copper), but has lower fat content which makes it a healthier choice for consumers (Naji et al, 2013). These nutritional advantages made broiler meat a major part of our diets (Arshad et al, 2016) and therefore increased the pressure on broiler industry for higher meat yield globally. Additionally, consumer preference changed from the whole bird to their processed parts, which further increased the importance of meat yield and its quality characteristics like tenderness, colour, water holding capacity and postmortem pH changes.…”
Section: Introductionmentioning
confidence: 99%
“…Current study indicated that color values increased with increasing the bioactive peptides supplementation level in feed. The higher color values indicated the red color of nuggets while lower color values indicated brown color of meat products (Arshad et al, 2016). Lowest values for shear force (N) of nuggets from broiler breast at 0 day (1,114) was observed in T 6 which gradually increased during storage period (1,129) at 45 th day of storage.…”
Section: Physico-chemical and Quality Characteristics Of Broiler Nuggetsmentioning
confidence: 98%